2009
DOI: 10.1038/sj.bjc.6605255
|View full text |Cite
|
Sign up to set email alerts
|

Epoetin-β treatment in patients with cancer chemotherapy-induced anaemia: the impact of initial haemoglobin and target haemoglobin levels on survival, tumour progression and thromboembolic events

Abstract: BACKGROUND: Epoetin-b is used to treat patients with cancer undergoing chemotherapy to alleviate the symptoms of anaemia, reduce the risk of blood transfusions and improve quality of life (QoL). METHODS: This meta-analysis of all 12 randomised, controlled studies of epoetin-b evaluated the impact of therapy at different Hb-initiation levels and to different target Hb levels on overall survival, tumour progression and thromboembolic events (TEE). An analysis of risk factors pre-disposing patients to TEEs under… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
29
0

Year Published

2011
2011
2019
2019

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 48 publications
(29 citation statements)
references
References 50 publications
0
29
0
Order By: Relevance
“…In summary, there have been a large number of trials investigating ESAs for the treatment of CIA in cancer patients (5,(10)(11)(12)(13)(14)(15)32). In several trials, an increase in thrombotic events was seen in the ESA arm (6,8,11,54).…”
Section: Discussionmentioning
confidence: 99%
See 4 more Smart Citations
“…In summary, there have been a large number of trials investigating ESAs for the treatment of CIA in cancer patients (5,(10)(11)(12)(13)(14)(15)32). In several trials, an increase in thrombotic events was seen in the ESA arm (6,8,11,54).…”
Section: Discussionmentioning
confidence: 99%
“…More importantly, meta-analyses show a decrease in overall survival in the ESA arm of some studies (6,8). This has prompted concern about the use of rHuEPO in cancer patients with anemia because, although the cause of this decreased survival is unknown, it has been speculated that the administration of rHuEPO may cause cancer progression (8,10). This preclinical study aimed to shed some light on the observed clinical effect of rHuEPO by investigating the expression and function of EPOR in preclinical model systems of human breast cancer metastasis.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations